Extremely large displacement dynamic analysis of elastic-plastic plane frames. - Wang, Ren-Zuo
This paper presents a numerical analysis of large displacement responses of elastic plastic plane frames under static and dynamic loads, by applying the vector form intrinsic finite element (VFIFE or V-5) method. The VFIFE method defines the structure into a number of mass points, and applies Newton's second law and the internal force equilibrium to describe the motions of each mass point. By tracing the motions of all the mass points, it can analyze the large geometrical and material nonlinear changes during the motion of the structure without using the geometrical stiffness matrix and iterative procedures. Three different numerical examples are presented to demonstrate both the capability and the accuracy of the VFIFE method in a nonlinear dynamic analysis of frame structures with extremely large displacement.
Keywords: Elastic plastic plane frame; Vector form intrinsic finite element; Extremely large displacement